2021
DOI: 10.3310/hta25090
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioural therapy for a variety of conditions: an overview of systematic reviews and panoramic meta-analysis

Abstract: Background Cognitive–behavioural therapy aims to increase quality of life by changing cognitive and behavioural factors that maintain problematic symptoms. A previous overview of cognitive–behavioural therapy systematic reviews suggested that cognitive–behavioural therapy was effective for many conditions. However, few of the included reviews synthesised randomised controlled trials. Objectives This project was undertaken to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 499 publications
2
20
0
1
Order By: Relevance
“…The present study is an extension of an overview of CBT for all health conditions (CBT-O), (Fordham et al, 2021a;Fordham et al, 2021b).…”
Section: Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…The present study is an extension of an overview of CBT for all health conditions (CBT-O), (Fordham et al, 2021a;Fordham et al, 2021b).…”
Section: Search Strategymentioning
confidence: 99%
“…The full methods of the CBT-O study have been previously published (Fordham, Suganvam, et al, 2021a). Where applicable, we adhered to the CBT-O protocol and did not produce a separate protocol for this 3.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, contemporary pain education is grounded in educational and learning science principles, moving away from didactic or 'information provision' approaches. It is also distinct from 'cognitive therapy' because it seeks to raise understanding of the biological processes underpinning pain rather than challenge negative patterns of thought about oneself or the world [72]. Relevant here is that the impetus for developing contemporary pain science education was in part the limitation of cognitive behavioural therapy in challenging unhelpful thoughts and behaviours.…”
Section: The Potentially Powerful Role Of Contemporary Pain Science E...mentioning
confidence: 99%
“…Although various studies have shown the effectiveness of evidence-based treatments (EBTs), including cognitive-behavioral treatment (CBT), in improving emotional problems (14)(15)(16), this approach has major weaknesses that have created limitations in the continuation of the treatment and its effectiveness. Some of the limitations of these treatments, which necessitate the emergence and use of new treatments for children, include: The existence of multiple treatment approaches for each disorder and passing multiple and longterm internship periods to become pro cient in implementing these treatments for each of the anxiety and mood disorders, the complexity of the treatment process due to overlapping symptoms and high comorbidity of EDs, and the failure of this treatment to improve a large number of disorders (especially comorbid disorders) (17).…”
Section: Introductionmentioning
confidence: 99%